Evaluate the Racecadotril Efficacy in Contrast the Reatment of Acute Diarrhea with Tril Compared to Probiotics and Loperamide in Adults - Agha Wali, Muhammad Naeem Aslam, Sohail Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study's objective is to compare the efficacy, safety, and acceptability of racecadotril to that of probiotics and loperamide in the treatment of patients with severe diarrhea. Study Design: A cross-sectional study Place and Duration: Conducted at Department of Gastroenterology Mayo Hospital Lahore, during from the period Sep 2021 to Feb 2022. Methods: There were 150 patients of both genders had age 18-60 years with acute diarrhea included in this study. After obtaining informed written consent detailed demographics of enrolled cases were recorded. Patients were equally divided in three groups. Group I received 2mg probiotics among 50 patients, group II received 2mg loperamide in 50 patients and 50 patients of group III received 100 mg acetorphan (racecadotril) three times a day. Patients were continuously received oral rehydration therapy for 3-days. Outcomes were assessed in terms of efficacy and complications among three groups.SPSS 22.0 was used to analyze complete data. Results: Among 150 presented case, majority of the patients were males 88 (58.7%) and the rest of the patients 62 (41.3%) were females. 60 (40%) patients had age 18-28 years, 40 (26.7%) had age 29-38 years, 30 (20%) had age 39-50 years and 20 (13.3%) had age >50 years. Majority of the cases had poor socio-economic status 90 (60%). We found that effectiveness of racecadotril 47 (94%) and loperamide 42 (84%) is significantly higher as compared to probiotics 15 (30%) with p value <0.005. Complications in group II was higher found in 18 (36%) cases as compared to group I 4 (8%) and 1 (2%) in group I. Conclusion: We concluded that loperamide and racecadotril are fast, effective treatments for acute diarrhoea. Probiotics are less effective than other medications yet have fewer adverse effects. Loperamide group had higher treatment-related constipation complications than others.